(untitled) (Research, Society and Development, 2023)
This article aimed to understand the contribution of ABA in the inclusion of children with ASD in the school environment. The study in question is of a qualitative nature, specifically a bibliographic-narrative type, where a literature search was conducted using the digital tool - Google, with search descriptors such as "the importance of ABA in school" or "the contribution of ABA in student inclusion in school." Subsequently, only the research studies with titles containing information relevant to the objective of this research were considered. As a result, eight studies were gathered, including six articles and two undergraduate theses. Therefore, through this survey, it was concluded that the found research studies reinforce the contribution of ABA in the educational environment, which promotes inclusion. This contribution is related to the development of autonomy and cognitive abilities of autistic children, as well as their social participation. To achieve these benefits, changes in pedagogical strategies are necessary, such as ongoing training of teachers in ABA, adapted curriculum, and a collaborative and well-coordinated effort among all professionals involved in the child’s learning process.